2019
DOI: 10.3389/fsufs.2019.00060
|View full text |Cite
|
Sign up to set email alerts
|

Measuring What Matters: Actionable Information for Conservation Biocontrol in Multifunctional Landscapes

Abstract: Despite decades of study, conservation biocontrol via manipulation of landscape elements has not become a mainstream strategy for pest control. Meanwhile, conservation groups and governments rarely consider the impacts of land management on pest control, and growers can even fear that conservation biocontrol strategies may exacerbate pest problems. By finding leverage points among these actors, there may be opportunities to align them to promote more widespread adoption of conservation biological control at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…Despite the success shown by local conservation biological control techniques [ 11 , 12 ], ecologists, agronomists, and farmers are increasingly recognizing the critical role that surrounding landscape can play in determining pest damage [ 13 ]. Simple and homogeneous landscapes are generally originated from mass-production agricultural systems, defined by continuously extended agricultural fields and by reduced diversity of vegetation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the success shown by local conservation biological control techniques [ 11 , 12 ], ecologists, agronomists, and farmers are increasingly recognizing the critical role that surrounding landscape can play in determining pest damage [ 13 ]. Simple and homogeneous landscapes are generally originated from mass-production agricultural systems, defined by continuously extended agricultural fields and by reduced diversity of vegetation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…As such, failing to monitor pests throughout the growing season may obscure population dynamics and mask landscape effects (Chaplin‐Kramer et al ., 2013). Similarly, failing to sample across broad spatial scales, for multiple years, may miss the rare but severe outbreaks that farmers care about (Chaplin‐Kramer et al ., 2019). In addition, most landscape studies focus on broad land‐cover classes rather than remotely sensed measures that could more directly encapsulate pests’ niches (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, agroecologists rarely measure the key pest‐control variables that drive land management decisions (Chaplin‐Kramer et al ., 2019). Most studies focus on natural enemies, and the fewer studies that focus on pests usually quantify relative pest abundances between sites (Bianchi et al ., 2006; Gurr et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have demonstrated that diverse fields (Letourneau et al, 2011;Dassou and Tixier, 2016) and landscapes (Chaplin-Kramer et al, 2011;Dainese et al, 2019) can promote more natural enemies and fewer pests than monocropped systems, it is by no means a guarantee (Tscharntke et al, 2016;Karp et al, 2018). Uncertainty about the effectiveness of habitat management, high risk aversion, and perception of non-crop habitat as a likely source of pests make farmers wary of adopting preventative pest management approaches (Salliou and Barnaud, 2017;Chaplin-Kramer et al, 2019;Shields et al, 2019). The challenge for agroecologists is to improve the scientific basis for habitat management while accounting for the context-dependency of pest and natural enemy dynamics (Settele and Settle, 2018).…”
Section: Introductionmentioning
confidence: 99%